Rhizina undulataFr.(Ascomycota, Pezizales) in post-fire succession on the Oleschkivs’ki Sands of Kherson region (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Data about the new for the southern Ukraine pathogenic fungus Rhizina undulataFr. are provided. The fungus caused illness and following total death of pine-trees seedlings, which were planted in a fall-winter period 2007-2008 in order to replace artificial pine forest (Pinus sylvestris L. , P. pallasianaD. Don.) that had burned out during forest conflagrations in August 2007.
Keywords: Rhizina, pine forest, root patogen, Kherson region, Ukraine.